Suitability of natural sounds to enhance soundscape quality in urban residential areas - Hong, Joo-Young (2017)
Masking noise by introducing pleasant natural sounds is one of the soundscape design approaches to improve soundscape quality. In order to achieve good soundscape quality, it is necessary to consider both pleasantness and suitability of maskers. This study aims to investigate the effects of main functions of places on suitability of natural sounds to mask traffic noises. Thirteen natural sounds including birds, insects and water sounds were used as acoustic stimuli. Spherical panoramic pictures of six locations in residential areas were captured for laboratory experiment. The laboratory experiments consisted of audio-only, visual- only, and audio-visual conditions. In the audio-only session, pleasantness of natural sounds were assessed, and suitable behavioural activities in the six locations were evaluated in the visual-only session. In the audio-visual session, suitability of the natural sounds as maskers were evaluated in the six different locations. The results showed that suitability of masker is significantly influenced by the contexts of the places in residential areas.